Machine learning and network-based approaches unveil key aspects of gene regulation that drive Plasmodium falciparum pathogenesis - Birkholtz, Lyn-Marie (University of Pretoria, 2022)
Thesis (PhD (Biochemistry))--University of Pretoria, 2021.